PENGARUH KUALITAS TIDUR TERHADAP TINGKAT PRODUKTIVITAS MAHASANTRI DI LINGKUNGAN LEMBAGA TINGGI PESANTREN LUHUR MALANG - Natasyah Asviana; Mustofa; Yasri Rahmawati; Tsaabitah Jihaan Sabrina; Ayesa Zahwa Amelia; Aditia Dhani Mustofa (Jurnal Studi Pesantren, 2026)
Sleep is a primary need that plays an important role in maintaining body functions to continue to run properly. The density of daily activities and rhythms in the Islamic boarding school environment often requires good time management. However, in reality, rest patterns and sleep quality are less noticed, such as sleeping late at night because of college assignments, organizational activities or committee activities that become routine. This study aims to analyze the relationship between sleep quality and the productivity of collage students at the Luhur Malang Islamic Boarding School. This study uses a quantitative observational analytical research type with a cross-sectional approach that was carried out in May 2025 at the Luhur Malang Islamic Boarding School. The number of samples successfully collected in this study was 90 collage students. The data obtained were then processed by calculating the average value of each variable (sleep quality and productivity) and then a correlation was carried out between the two. The average value is then divided into three levels, namely: low (1.00-2.99), medium (3.00-3.99), and high (4.00-5.00). Then the Pearson correlation test was carried out using statistical software, namely SPPS. The results obtained for the low sleep quality category were 61 people (67.8%), and 29 people (32.2%) with a correlation coefficient of the two variables of r = 0.988 with a significance value of p = 0.001. This means that there is a positive relationship between sleep quality and productivity levels. This has a direct impact on sleepiness in the morning. As a result, poor sleep quality is one of the causes of decreased collage student productivity.